Arbitrage, Covered Interest Parity and Cointegration Analysis on the NTD/USD Forex Market Revisited - Kuo-Shing, Chen; Chun-Ming, Chen; Chien-Chiang, Lee (International Journal of Economics and Financial Issues, 2017)
This study applies interest parity theory including Covered Interest Parity (CIP) to examine the 30-, 60-.90-, and 180-day maturities for the NTD/USD foreign exchange (FX) market. In the empirical unit root tests, we find that NTD/USD forward premium and interest rate spread present I(0) property. Empirical results are provided that interest rate differential appears stationary component; imply the stable relationship between Taiwan and USA on monetary policy. Using Taylor (1989)'s covered interest arbitrage model, the empirical results exhibit the absence of excess profit opportunities on New Taiwan Dollar (NTD) or US Dollar (USD) returns. Additionally, theoretical innovation approach of the cost-of-carry model is considered to evaluate the arbitrage opportunities in FX study. Accordingly, the covered interest parity condition generally continue to hold that almost zero-arbitrage results support FX market efficiency although the Federal Reserve implemented several rounds of quantitative easing after the peak of the 2008 financial crisis. Ultimately, Taiwanese FX market emerges to have been little affected by the increased crisis risks during the turbulent times because of the its limited development and market integration. Keywords: Covered Interest Parity, Market Integration, Granger Causality Tests, Cost-of-Carry model JEL Classifications: G1, G12, F32